Usefulness of Diagnostic Staging Laparoscopy for Advanced Gastric Cancer. Issue 4 (April 2023) - Yoshikawa, Kozo; Shimada, Mitsuo; Higashijima, Jun; Tokunaga, Takuya; Nishi, Masaaki; Takasu, Chie; Kashihara, Hideya; Eto, Shohei; Yoshimoto, Toshiaki
Background: For advanced gastric cancer (AGC), peritoneal metastasis is the most common determinant of unresectability, but accurate preoperative diagnosis for peritoneal metastasis is challenging. Staging laparoscopy (SL) can detect unsuspected peritoneal metastasis. This study retrospectively evaluated the utility of SL and its indication in patients with AGC. Methods: In this study, we enrolled 114 patients with pathologically diagnosed gastric adenocarcinoma who underwent SL. Results: Of the 114 patients, 43 (37.7%) had peritoneal metastasis (P1 or CY1). Higher age, larger tumor size, type 4 GC, deeper tumor depth, elevated CA125, and ascites findings in preoperative CT were found to be significant predictors of peritoneal metastasis. In multivariate analysis, peritoneal metastasis was associated with type 4 GC (odds ratio [OR]: 6.11; 95% confidence interval [CI]: 1.87-19.8; P < .01) and ascites in CT (OR: 4.25; 95% CI: 1.48-12.1; P < .01). Conclusions: Staging laparoscopy is an effective tool to detect peritoneal metastasis from AGC. It can increase the curative resection rate and decrease unnecessary laparotomies.